Surgical and medical management of small bowel gastrointestinal stromal tumors: A report of the Dutch GIST registry. Issue 3 (March 2019) - Boonstra, P.A.; Steeghs, N.; Farag, S.; van Coevorden, F.; Gelderblom, H.; Grunhagen, D.J.; Desar, I.M.E.; van der Graaf, W.T.A.; Bonenkamp, J.J.; Reyners, A.K.L.; van Etten, B.
Abstract: Background: A cohort of 201 patients with small bowel gastrointestinal stromal tumors (GIST) treated between January 1st, 2009 and December 31st, 2016 in five GIST expertise centers in the Netherlands was analyzed. Goal of this study was to describe the clinical, surgical and pathological characteristics of this rare subpopulation of GIST patients, registered in the Dutch GIST registry. Methods: Clinical outcomes and risk factors of patients with small bowel GIST who underwent surgery or treated with systemic therapy were analyzed. A classification was made based on disease status at diagnosis (localized vs. metastasized). Results: 201 patients with small bowel GIST were registered of which 138 patients (69%) were diagnosed with localized disease and 63 patients (31%) with metastatic disease. Approximately 19% of the patients had emergency surgery, and in 22% GIST was an accidental finding. In patients with high risk localized disease, recurrence occurred less often in patients who received adjuvant treatment (4/32) compared to patients who did not (20/31, p < 0.01). Disease progression during palliative imatinib treatment occurred in 23 patients (28%) after a median of 20.7 (range 1.8–47.1) months. Ongoing response was established in 52/82 patients on first line palliative treatment with imatinib after a median treatment time of 30.6 (range 2.5–155.3) months. Conclusion: Patients with small-bowel GIST more frequently present with metastatic disease when compared to patients with gastric GIST in literature. We advocate for Prospective registration of these patients and investigate the use of surgery in patients with limited metastatic disease. Abstract : A cohort of 201 patients from the Dutch GIST registry with small bowel GIST treated in expert centers between January 1st, 2009 and December 31st, 2016 was analyzed.